The complete chloroplast genome of Clematis henryi var. ternata (Ranunculaceae). Issue 4 (3rd April 2021) - Chen, Xiang; Chang, Qinxiang; Xia, Pengguo; Liang, Zongsuo; Yan, Kaijing
Abstract: The complete chloroplast genome of Clematis henryi var.ternata was determined in this study. The genome was 159, 675 base pair (bp) in length, containing a large single-copy (LSC) region of 79, 443 bp, a small single-copy region (SSC) of 18, 100 bp and a pair of inverted repeats (IRs) of 31, 066 bp. It contains 130 unique genes, including 86 protein-coding genes, 36 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The GC content of the complete chloroplast genome sequence was 38.0%. Phylogenetic analyses using complete chloroplast genomes showed that Clematis henryi var.ternata is most closely related to Clematis guniuensis (NC_050373.1).